Models of health behaviour predict intention to use long-acting reversible contraception. (November 2016) - Roderique-Davies, Gareth; McKnight, Christine; John, Bev; Faulkner, Susan; Lancastle, Deborah
The aim of this study was to investigate women's intention to use long-acting reversible contraception using two established models of health behaviour: the theory of planned behaviour and the health belief model. A questionnaire was completed by a convenience sample of 128 women attending a community sexual health clinic. The independent variables were constructs of theory of planned behaviour (attitude, subjective norm and perceived behavioural control) and health belief model (perceived susceptibility, perceived severity, perceived benefits, perceived barriers, health motivation and cues to action). The dependent variable was intention to use long-acting reversible contraception. The theory of planned behaviour and the health belief model accounted for 75% of the variance in intention to use. Perceived behavioural control, perceived barriers and health motivation predict the use of long-acting reversible contraception. Public health information for women considering using long-acting reversible contraception should be based around addressing the perceived barriers and promoting long-acting reversible contraception as a reliable contraceptive method.